Banach *-algebras generated by semicircular elements induced by certain orthogonal projections - Ilwoo Cho; Palle E. T. Jorgensen (Opuscula Mathematica, 2018)
The main purpose of this paper is to study structure theorems of Banach \(*\)-algebras generated by semicircular elements. In particular, we are interested in the cases where given semicircular elements are induced by orthogonal projections in a \(C^{*}\)-probability space.